Tourism Industry Performance: The role of local government in West Nusa Tenggara - Harsono, Iwan (JEJAK, 2024)
Mandalika is located on the south coast of Lombok Island, West Nusa Tenggara (NTB) Province, Indonesia, and is a major tourist destination in this area.  Tourism is one of the drivers of NTB's regional economic growth.  One of the main highlights of Mandalika is hosting the MotoGP racing series. Mandalika International Street Circuit was built in this area and became one of the first MotoGP race tracks in Indo-nesia. The government has an important role in promoting and marketing Mandalika tourist destinations. Through effective promotional campaigns, participation in tour-ism fairs, and cooperation with airlines and travel agencies, the government can increase Mandalika's visibility and attractiveness at national and international levels.  However, some parties feel that the role of the government is still lacking in improving the performance of the tourism industry in the regions. This research was conducted in the Mandalikan tourist area and aims to analyze the role of the government in improving the performance of the tourism industry in the Mandalika tourist area. This study used quantitative methods. The sample in this study was 97 respondents. The results of this study found that the role of the government has improved the perfor-mance of the tourism industry in the Mandalika Area.